NUME ŞI IDENTITATE. ANALIZA ONOMASTICII DIN ŢARA ROMÂNEASCĂ ÎN SECOLELE XIV-XVI (IDENTITĂȚI COLECTIVE ȘI IDENTITATE NAȚIONALĂ. PERCEPȚII ASUPRA IDENTITĂȚII ÎN LUMEA MEDIEVALĂ ȘI MODERNĂ. ln memoriam Alexandru Duţu, 2026)
The author has undertaken the statistical analysis of the names included in the Wallachian documents from the late 14th century up to 1550. She has found 6418 mentions of 1587 names. She has taken into consideration four aspects: the etymology of the names ( distinguishing names of Christian, Slavic, Romanian, Hungarian, Turkish-Cumanian, Greek and other origin), the geographical distribution (she has divided Wallachia in 4 areas), gender, and the social background of the people having these names (boyars, clergy, townsmen, peasants, Gypsy slaves).